Exchange Rate Shocks and Sectoral Stock Returns in Nigeria: Do Asymmetry and Structural Breaks Matter? - Ismail Olaleke Fasanya; Oluwafunmilayo A. Akinwale (Cogent Economics & Finance, 2022)
This study examines the effect of exchange rate shocks on ten (10) sectoral stock returns in Nigeria from January 2007 to December 2018. The autoregressive distributed lag and nonlinear autoregressive distributed lag are employed to examine symmetric and asymmetric relationship between exchange rate and sectoral stock returns. The result shows that only financial service sector moves in an asymmetric fashion in the short and long period without taking account of structural breaks and with structural breaks, none of the sectoral stock returns were asymmetric. The result shows that exchange rate movement affects the sectors differently. Therefore, this study concludes that a single model cannot fit all the sectoral stock returns because all sectors respond differently to exchange rate movements and the information about a particular sector cannot be used to forecast other sectors. These results offer important insights for investors, regulators and policymakers.
Keywords: 330; Exchange rate; stock returns; Asymmetry; structural breaks